2013
DOI: 10.1002/app.39601
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the antibacterial activity of natural rubber latex foam by the incorporation of zinc oxide nanoparticles

Abstract: The synthesis and characterization of ZnO-nanoparticle-incorporated natural rubber latex foam (NRLF) are described in this article. ZnO nanoparticles were added as the primary gelling agent by the replacement of the microsized ZnO particles, whereas the control sample of the NRLF was made without the addition of any ZnO particles. ZnO nanopowder was evaluated by X-ray diffraction (XRD), whereas the aqueous dispersion of nano-ZnO was evaluated by transmission electron microscopy (TEM) micrograph analysis. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 32 publications
0
31
0
4
Order By: Relevance
“…[1][2][3] Many approaches have been discussed to deal with bacteria's antibiotic resistance and many antibacterial agents, especially inorganic nanoparticles, 4 e.g. [15][16][17] Signicant studies indicated that silver nanoparticles have strong antibacterial effects because of their high antibacterial activity and broad antibacterial spectrum even at low concentrations, [18][19][20] and relative nontoxicity to human cells. [15][16][17] Signicant studies indicated that silver nanoparticles have strong antibacterial effects because of their high antibacterial activity and broad antibacterial spectrum even at low concentrations, [18][19][20] and relative nontoxicity to human cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Many approaches have been discussed to deal with bacteria's antibiotic resistance and many antibacterial agents, especially inorganic nanoparticles, 4 e.g. [15][16][17] Signicant studies indicated that silver nanoparticles have strong antibacterial effects because of their high antibacterial activity and broad antibacterial spectrum even at low concentrations, [18][19][20] and relative nontoxicity to human cells. [15][16][17] Signicant studies indicated that silver nanoparticles have strong antibacterial effects because of their high antibacterial activity and broad antibacterial spectrum even at low concentrations, [18][19][20] and relative nontoxicity to human cells.…”
Section: Introductionmentioning
confidence: 99%
“…A broaden peak is observed in the n ‐SiO 2 and SSBR/ n ‐SiO 2 composites, indicating the existence of amorphous silica . Similarly, the other peaks cannot be found in the SSBR/N660 sample except for the peaks of the ZnO, corresponding to (100), (002), and (101) lattice planes of ZnO wurtzite hexagonal structure, indicating that only the highly disordered structure of carbon black N660 exists in the SSBR matrix. In addition, the XRD patterns show that the crystal structure of m‐ SiO 2 was mostly preserved and not affected significantly in SSBR matrix.…”
Section: Resultsmentioning
confidence: 91%
“…Sedangkan penambahan 2% ZnONP mampu meningkatkan persentase kristalin dari foam meskipun kecil. Hasil ini sejalan dengan yang dilaporkan oleh Rathnayake et al 22 , bahwa ZnONP pada foam dari karet latex alami dapat meningkatkan bagian kristalin. Penambahan EG dapat meningkatkan persentase kristalin foam tanpa penambahan dari ZnONP.…”
Section: Kristalinitasunclassified